Overview of Vaccination Trials for Control of Tuberculosis in Cattle, Wildlife and Humans. (31st October 2013) - Buddle, B. M.; Parlane, N. A.; Wedlock, D. N.; Heiser, A.
Summary: Vaccination is a key strategy for control of tuberculosis (TB), and considerable progress has been made in the past 5 years to develop improved vaccines for humans and animals, differentiate vaccinated animals from those infected with Mycobacterium bovis and deliver vaccines to wildlife. Studies have moved from testing vaccines in small animal models to clinical trials in humans and from experimental challenge studies in cattle and wildlife to evaluation of vaccines in the field. Candidate vaccines undergoing testing in humans include live mycobacterial vaccines to replace bacille Calmette Guérin (BCG), subunit vaccines (virus vector or protein) to boost BCG and therapeutic vaccines used as an adjunct to chemotherapy. In cattle, a number of diagnostic tests have been developed and successfully tested for differentiating infected from vaccinated animals, which will facilitate the use of BCG vaccine in cattle. Encouraging results have been obtained from recent field trials in cattle using BCG vaccine to protect against natural exposure to M. bovis . To date, no subunit TB vaccines have induced improved protection compared with that for BCG, but prime–boost combinations of BCG with DNA, protein or virus‐vectored vaccines have induced better protection than BCG vaccine alone. Development of an oral bait BCG formulation has demonstrated the practicality of delivering TB vaccines to wildlife. Oral BCG preparations have induced protection against experimental challenge of M. bovis in possums, badgers, wild boar and white‐tailed deer and against natural exposure to M. bovis in possums. Recent progress in TB vaccine development has provided much impetus for their future use.